The Urgency Of Developing Law As A Legal Basis For The Implementation Of Artificial Intelligence In Indonesia - Chairani, Meirza Aulia; Pradhana, Angga Pramodya; Purnama, Taufiq Yuli (Law and Justice, 2022)
The presence of Artificial Intelligence in Indonesia currently has no statutory regulation that regulates it, but in several sectors in the field of Information Technology, Artificial Intelligence has been developed in Indonesia. Some developed countries already use Artificial in the field of law, such as advocacy, making laws and regulations, learning law, and so on. Objective: Applying Artificial Intelligence in Indonesia in the field of law to facilitate work in the legal field Methods: This research uses a normative juridical research method, a conceptual approach and a statutory approach. Findings: Artificial Intelligence can be used in Indonesia, not only in the legal field but also in all areas of ease of work and shortening of work. Function: the usefulness of this research is to assist in the legal field, facilitate the work of legal experts such as making laws and regulations which first take a long time to make, legal consultations for the public now do not need to come to lawyers or legal consultants can use Artificial Intelligence to provide consultations. consultation on legal matters. There have been many law offices abroad that have implemented Artificial Intelligence in their offices, if they are unable to attend to provide consultations to their clients, using Artificial Intelligence applications can already help provide solutions. Legal learning can also use Artificial Intelligence, already in Indonesia, pioneering legal learning for law students and the public who want to study law. Novelty: this research is related to Artificial Intelligence, it is still rare for people to know about its use in the legal field, therefore we made research related to Artificial Intelligence to provide information related to this.